Environmental Quality and Ecological Risk Assessment of Heavy Metals in the Zhuhai Coast, China - Wu, Jin; Rong, Shaowei; Wang, Miaowei; Lu, Rong; Liu, Jingchao (Frontiers in Marine Science, 2022)
The rapid urbanization and industrialization in the coastal of Zhuhai has resulted in a severe heavy metal contamination pressure. Heavy metals are extensively used as monitors of coastal contamination, but the comparability among different geographic environments needs to be further explored and scrutinized. In this study, heavy metals (i.e., As, Zn, Cd, Cr, Hg, Cu, and Pb) in surface seawater sediments, and organisms were analyzed to assess the distribution, enrichment, and ecological risk in the coastal of Zhuhai. The results showed that Cu, Zn, and Pb exceeded the standards of seawater, indicating the presence of anthropogenic pollution. Meanwhile, the ecological risk results based on species sensitivity analysis showed that Cd and Cu indicated moderately high environmental risk and heavy metals showed different trends in the quantity and quality of organisms in seawater and sediment in the sea, with a greater impact on organisms in the northeastern sea area. Therefore, preserving the high biological diversity in this area is important to ensure the health and productivity of the seawater ecosystem in the coastal area. These results may play a key role in promoting decision makers to manage the sustainability of the Zhuhai sea area.